Optimalisasi Biaya Distribusi pada TB Nur Barokah yang Berbasis UMKM di Indonesia dengan Penerapan Metode Transportasi - Muannisah, Nurul; Fitriyani, Lailatul; Dini Aurora H., Lintang; Fatchuroji, Alwi; Purwaningrum, Titis (PENG: Jurnal Ekonomi dan Manajemen, 2025)
TB Nur Barokah, as one of the main entities in the manufacturing sector, faces significant challenges in the form of high distribution costs due to inefficiencies in supply chain management. This study aims to develop a distribution optimization strategy through the application of transportation methods based on operations research. Approaches used include the North West Corner (NWC), Least Cost (LC), and Vogel's Approximation Method (VAM) to produce an efficient initial solution. Furthermore, the Stepping Stone and MODI methods are applied to ensure that an optimal solution is achieved. The results revealed that the systematic application of transportation methods was able to reduce distribution costs by 30%, increase delivery time efficiency by 20%, and contribute to increased customer satisfaction.